Rabbinic Judaism in the Making The Halakhah from Ezra to Judah I - Guttmann, Alexander (Wayne State University Press, 2018)
Through the ages, theology in Judaism has played roles of varying importance. But the role of theology is minor compared with that of law and observance. This book is devoted to a study of the evolution of normative Judaism from the time of Ezra (ca. 400 B.C.) to Judah I, the Prince (ca. 200 A.D.). Its focus on law represents a realistic approach to the history of applied Judaism. Rabbinic Judaism in the Making is the first study in English to trace the evolution of Rabbinic Law and Rabbinic Judaism. A concise history of post-biblical normative Judaism in antiquity, Mr. Guttmann's book concentrates on the crucial inter-testamental period, and should be valuable to students of ancient history, and both Christian and Jewish theologians, ministers, and rabbis.